1989
DOI: 10.1002/hyp.3360030107
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and concentration of suspended solids in the upper rhone river by continuous flow centrifugation

Abstract: Six stations along the RhBne River from the RhBne Glacier to Lake Geneva were sampled by continuous flow centrifuge for recovery of suspended sediment. The samples were taken four times in the year in both 1982 and 1983. In addition, the mouth of the river was sampled in a like manner every two weeks during 1982 until August 1983. Concentration of sediment and composition did not vary as a function of depth or location across the river. Concentrations varied in time and as a function of flow and samples showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 3 publications
(5 reference statements)
4
28
0
Order By: Relevance
“…, and one coarser at 396pm. These values agree well with data from Burrus (1989) and Santiago (unpublished) on longer-term sampling. The coarse sands transported in suspension or by saltation are moving as a result of the high hydrodynamic energy of the glacial waters and probably in conjunction with some resuspension due to gravel pits.…”
Section: Particle Sizesupporting
confidence: 91%
“…, and one coarser at 396pm. These values agree well with data from Burrus (1989) and Santiago (unpublished) on longer-term sampling. The coarse sands transported in suspension or by saltation are moving as a result of the high hydrodynamic energy of the glacial waters and probably in conjunction with some resuspension due to gravel pits.…”
Section: Particle Sizesupporting
confidence: 91%
“…This was necessary to provide sufficient sediment to carry out the total array of analyses required in the collaborative study. The efficiency of particle separation in these centrifuges is known to be greater than 90% of the incoming suspended sediment (McMillan & Thomas, 1977;Ongley & Blachford, 1982;Horowitz et al, 1989;Ongley & Thomas, 1989;Burrus et al, 1989). A comparative evaluation of the two centrifuges utilized indicates high similarity in the performance of both machines, which show comparable grain size distributions and heavy metal concentrations for the collected suspended solids (Santiago et al, 1990). Sediments were collected at 9 locations.…”
Section: Sediment Samplingmentioning
confidence: 99%
“…Investigations showed that the flow centrifuge Padberg Z61 (17 000 U/min) recovers 93 % of the suspended solids [16] in comparison to a filtration (0.45 μm pore width). Burrus et al [17] demonstrated that 97 % of the suspended solids could be recovered with Westfalia centrifuge compared to 0.45-μm filtration.…”
Section: Sampling Sitesmentioning
confidence: 98%